PAPAN PINTAR PROFESI: MEDIA PEMBELAJARAN SEBAGAI SARANA PENGENALAN KONSEP KARIR PADA SISWA KELAS IV SEKOLAH DASAR - A. Hari Witono; I Ketut Widiada; Mansur Hakim; Heri Hadi Saputra; Heri Setiawan (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2023)
The aim of this research is to develop a flannel board-based smart board to introduce career concepts in supporting elementary school teachers' duties in carrying out guidance and counseling. The type of research used is development research with a 4D model (define, design, develop, disseminate). The test subjects were guidance and counseling experts, media experts, elementary school teachers, and 9 students from class IV elementary school. The instruments used were expert feasibility and user practicality questionnaires. Data analysis was carried out using qualitative analysis for critical data and suggestions from experts and users, as well as quantitative analysis for values ​​from experts and users. The results of the BK expert test showed that the media developed received a score of 79.5 (decent) and the assessment of media experts and practitioners obtained a score of 82.5 (decent). The field test results obtained a score of 83 (practical). From the results of expert tests and field tests, it was concluded that the smart board media developed was suitable and practical for use in counseling and career guidance in elementary schools.